О ПРОБЛЕМЕ ОТБОРА УЧЕБНОГО МАТЕРИАЛА ПРИ ОБУЧЕНИИ ПРОФЕССИОНАЛЬНО-ДЕЛОВОМУ ОБЩЕНИЮ - Сейтенова, В.А. (SCIENCE and SOCIETY, 2018)
The article considers the issues of selection and presentation of the material in the Russian language for communication in the spheres of economics and business. The choice of the theme is dictated by the necessity of teaching spoken language for specific purposes in Russian. The principles of the selection of the linguistic content are determined by the criteria of making up the lexical minimum of professionally –directed language teaching. The criterias of selecting the lexical minimum can be the basis in writing manuals for broad circle of the businessmen who have business relations with Russia and other countries.
Keywords: the language for Specific Purposes; the communicative competence; business dialogue; basic word stock; the language maintenance of training; sphere of communication; criteria of the selection; thematic efficiency; semantics; economic terminology; lexeme; terms-set phrases; communicative meaning